Quantum surface-response of metals revealed by acoustic graphene plasmons - P. A. D. Gonçalves (Nature Portfolio, 2021)
Knowledge of the quantum response of materials is essential for designing light–matter interactions at the nanoscale. Here, the authors report a theory for understanding the impact of metallic quantum response on acoustic graphene plasmons and how such response could be inferred from measurements.